(untitled) (World Science, 2016)
The article discusses the basic requirements for the development of oil and gas condensate fields, methods, specific approach to the development of gas condensate fields and a comparative analysis of the conditions for the maximum condensate recovery from the reservoir. Presents problems and solutions about the appropriateness of the technology of gas stimulation fields in order to achieve the maximum rate of extraction of hydrocarbons.